2007
DOI: 10.1007/s00020-007-1509-x
|View full text |Cite
|
Sign up to set email alerts
|

Disintegration of Measures and Contractive 2-Variable Weighted Shifts

Abstract: In this paper we give a new proof of the existence of disintegration measures using the Hausdorff Moment Problem on a Borel measurable space X × Y , where X ≡ Y is the unit interval. Using this new tool, we can give an abstract solution, moreover, and a concrete necessary condition for the Lifting Problem for contractive 2-variable weighted shifts. In addition, we have a new, computable, and sufficient condition for the Lifting Problem for 2-variable weighted shifts, and an improved version of the Curto-Muhly-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…In the case when T is subnormal, the Berger measure μ of T is given by Although the lemma below is a known result (see [20]), we give the complete proof for the reader's convenience. …”
Section: Schur Product In Commuting 2-variable Weighted Shiftsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case when T is subnormal, the Berger measure μ of T is given by Although the lemma below is a known result (see [20]), we give the complete proof for the reader's convenience. …”
Section: Schur Product In Commuting 2-variable Weighted Shiftsmentioning
confidence: 99%
“…It is well known that the commutativity of the pair is necessary but not sufficient [1,[15][16][17], and it has recently been shown that the joint hyponormality of the pair is necessary but not sufficient [10]. In previous work we gave abstract solutions ([6, Theorem 3.1], [20,Theorem 2.7]) and concrete necessary conditions, albeit not sufficient, for the lifting ( [11,Theorem 3.3], [20,Theorem 2.10]) for 2-variable weighted shifts. In this paper we study the hyponormality and subnormality of 2-variable weighted shifts using the Schur product techniques in matrices.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…, n ( [8]). Because the structure of ntuple operators can be extended from the study of 2-tuple operators, many operator theorists have concentrated their studies to the structure of n-tuple operators (see [3], [4], [5], [6], [7], [9], [10], [11], [12], [13], etc.). Curto, Lee and Yoon considered the properties (such as, hyponormality, subnormality, flatness, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In [10], Curto, Muhly and Xia conjectured that if T = (T 1 , T 2 ) is a pair of commuting subnormal operators on H, then the hyponormal condition of T is enough for the subnormality of T. In many recent papers containing ( [6], [7], [8][11], [12], [18]), the conjecture was showed negatively. Example 2.9 is also a simple new counterexample for the Curto-Muhly-Xia conjecture.…”
mentioning
confidence: 99%